Presenting a Structural Model of Wisdom in Couples Based on Moral Intelligence with the Mediating Role of Mindfulness - Radnia, Mahdieh; Dortaj, Fariborz; Nasrolahi, Bita; Kashani Vahid, Leila (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to present a structural structural model of wisdom in couples based on moral intelligence with the mediating role of mindfulness. Methods: The research method is cross-sectional correlation. The statistical population of this study consisted of all couples (couple) in Tehran in 1300-1400, from which 380 people were selected by stepwise cluster sampling. In this study, the tools of wisdom (Ardelt, 2003), moral intelligence (Lenick and Kiel, 2011), and mindfulness (Ryan and Brown, 2003) All of them had acceptable validity and reliability. SPSS-V23 and Amos-V8.8 software were used to analyze the data. Structural equation modeling was also used to answer the research hypotheses. Results: Findings showed that the model has a good fit. The results showed that moral intelligence had a direct effect on wisdom, the relationship between moral intelligence and wisdom is directly equal (t = 4.63 and β = 0.51). The results also showed that the indirect effect of moral intelligence on the wisdom of the couple was confirmed by mindfulness with 95% confidence. Conclusion: Therefore, this model can be a good model for identifying the factors affecting couples’ wisdom and its results can be used in planning to increase mindfulness and moral intelligence in couples. Therefore, paying attention to the mentioned variables in prevention and designing more appropriate therapies will help researchers and therapists.